1992
DOI: 10.1029/91jc02014
|View full text |Cite
|
Sign up to set email alerts
|

Primary production estimates from recordings of solar‐stimulated fluorescence in the equatorial Pacific at 150°W

Abstract: Biological, optical, and hydrographical data were collected on the WEC88 cruise along 150 ø W and during a 6-day time series station on the equator during Februaxy/Maxch 1988. This axea was chaxacterized by a subsurface chlorophyll maximum (SCM), located at 50-70 m depth at the equator and descending down to 120-125 m at the north and south end of the transect. Highest primaxy production rates were neax-surface and confined to the equatorial region and stations between 7 ø and 11øN. To determine the relationsh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 34 publications
1
15
0
Order By: Relevance
“…Maximum Qi, for shallow populations in Lake Bonney was 2-3 times higher in January than in November or December (Table 1). It is not clear whether this response indicates nutrient starvation like a batch culture (unbalanced growth) or nutrient limitation at steady state like a chemostat (balanced growth), but Cullen et al (1992) suggested that the former scenario is more likely to produce variations in @'c related to nutrient supply.…”
Section: Discussion and To A Lesser Degree By Increasing @Y Valuesmentioning
confidence: 99%
“…Maximum Qi, for shallow populations in Lake Bonney was 2-3 times higher in January than in November or December (Table 1). It is not clear whether this response indicates nutrient starvation like a batch culture (unbalanced growth) or nutrient limitation at steady state like a chemostat (balanced growth), but Cullen et al (1992) suggested that the former scenario is more likely to produce variations in @'c related to nutrient supply.…”
Section: Discussion and To A Lesser Degree By Increasing @Y Valuesmentioning
confidence: 99%
“…Regardless, field measurements of solar-induced fluorescence have been related to chlorophyll and photosynthesis under a variety of conditions (e.g. Gower et al 1984;Kiefer et al 1989;Stegmann et al 1992;Gitelson et al 1994;Abbott et al 1995).…”
Section: Critical Applications For Hab Researchmentioning
confidence: 99%
“…Studies that have examined the relationship between F nat and different aspects of primary production and photosynthesis (e.g., Kiefer et al 1989;Stegmann et al 1992;Garcia-Mendoza and Maske 1996) have failed to identify a robust relationship between F nat and phytoplankton growth. The lack of a simple relationship between F nat yield and photosynthetic processes in phytoplankton reflects the complexity of light absorption and fluorescence in vivo.…”
mentioning
confidence: 99%